Antimicrobial use, drug-resistant infections and COVID-19 - Rawson, Timothy M. (Nat Rev Microbiol, 2020)
Coronavirus disease 2019 may have a complex long-term impact on antimicrobial resistance (AMR). Coordinated strategies at the individual, health-care and policy levels are urgently required to inform necessary actions to reduce the potential longer-term impact on AMR and on access to effective antimicrobials.